KOMUNIKACJA PACJENT-LEKARZ W PLACÓWKACH OCHRONY ZDROWIA CZ. II - Drop, Katarzyna Magdalena; Drop, Bartłomiej; Skolimowski, Michał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Communication, in every form is the inseparable element of daily life. In this connection it is also responsible for the corresponding construction of the bond between the participants of therapeutic and curative process - by a patient and a doctor. These days we have general and unlimited access to information, that is why every patient is capable itself to find, by numerous medias a lot of information about new medical possibilities and nascent complications of their illness. This is the reason why, nowadays there is a necessity of giving detailed knowledge about the illness and possible methods of treatment to all patients. A patient expects explaining why such, but not other method of treatment is recommended and why certain medications are prescribed by a doctor to him. Very often doctors talk in an incomprehensible method to their patients, using a medical nomenclature only. Patients do not ask questions, even when they do not understand the details given by a doctor. To attain ability of corresponding construction of report between both participants of treatment process there is a need of improvement of communication abilities. The aim of this survey was to research and describe widespread reports between patients and doctors. The other aim was to determine a role of communication and her influence on their construction. The mentioned below work is continuation of publication: “ Physician–patient communication in healthcare facilities, part I”., that presented theoretical honor of reflections on the theme of influence of communication between participants of the curative process on the state of health and satisfaction of final recipient of services - patients. The results of the questionnaire, conducted among 100 patients touches mentioned above an experience theme, will be discussed in-process. Research was conducted in the Lublin representative offices of health protection. The worked out results and suggestions can and must serve to the patients as well as doctors in the further process of perfection of these reports.